Cloud–cloud collision as drivers of the chemical complexity in Galactic Centre molecular clouds. Issue 4 (29th July 2020) - Zeng, S; Zhang, Q; Jiménez-Serra, I; Tercero, B; Lu, X; Martín-Pintado, J; de Vicente, P; Rivilla, V M; Li, S
ABSTRACT: G+0.693-0.03 is a quiescent molecular cloud located within the Sagittarius B2 (Sgr B2) star-forming complex. Recent spectral surveys have shown that it represents one of the most prolific repositories of complex organic species in the Galaxy. The origin of such chemical complexity, along with the small-scale physical structure and properties of G+0.693-0.03, remains a mystery. In this paper, we report the study of multiple molecules with interferometric observations in combination with single-dish data in G+0.693-0.03. Despite the lack of detection of continuum source, we find small-scale (0.2 pc) structures within this cloud. The analysis of the molecular emission of typical shock tracers such as SiO, HNCO, and CH3 OH unveiled two molecular components, peaking at velocities of 57 and 75 km s −1 . They are found to be interconnected in both space and velocity. The position–velocity diagrams show features that match with the observational signatures of a cloud–cloud collision. Additionally, we detect three series of class I methanol masers known to appear in shocked gas, supporting the cloud–cloud collision scenario. From the maser emission we provide constraints on the gas kinetic temperatures (∼30–150 K) and H2 densities (10 4 –10 5  cm −2 ). These properties are similar to those found for the starburst galaxy NGC 253 also using class I methanol masers, suggested to be associated with a cloud–cloud collision. We conclude that shocks driven by the possible cloud–cloud collision is likely the most important mechanism responsible for the high level of chemical complexity observed in G+0.693-0.03.